Quantification of the BOLD response via blood gas modulations - Croal, Paula L. (2014)
This thesis is intended to contribute to a quantitative understanding of the blood oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) signal in order to increase its clinical potential. Here, the vascular, neuronal and physical processes which combine to give a resulting BOLD signal are investigated using respiratory challenges. The effect of isocapnic hyperoxia on vascular responses is investigated at 7 Tesla. No significant change was found in resting-state cerebral blood flow (CBF), resting-state cerebral blood volume (CBV) and task-evoked CBF. This challenges a previously held idea that hyperoxia is vasoconstrictive. The effect of isocapnic hyperoxia on neuronal oscillations was assessed with magnetoencephalography (MEG). Whilst a significant reduction in oscillatory power is reported in the occipital lobe, the change is significantly smaller than the global reduction previously measured with hypercapnia. These findings suggest that hyperoxia is an ideal tool for calibrated BOLD fMRI. The relationship between the change in blood oxygenation and change in transverse relaxation plays a key role in calibrated BOLD fMRI. However, previous measurements have been confounded by a change in CBV. Here, the relationship was found to be sub-linear across 1.5, 3 and 7 Tesla. Previous results which suggest a supralinear relationship at 1.5/3 Tesla and a linear relationship at 7 Tesla, are attributed to the relative contribution of intravascular/extravascular signals and their dependence on field strength, blood oxygenation and echo time. Finally, a comparison of single and multiphase ASL is made at 7 Tesla, with a modified Look-locker EPI sequence presented which allows simultaneous measurement of CBF and transit time, whilst increasing the available BOLD signal. This could have important implications for hypercapnia calibrated BOLD fMRI, where choice of ASL sequence may affect the estimated change in CMRO2. Furthermore, it provides a framework for future cerebral haemodynamic studies where simultaneous measurements are required.